The real exchange rate, innovation and productivity: Regional heterogeneity, asymmetries and hysteresis - Laura Alfaro; Alejandro Cu\~nat; Harald Fadinger; Yanping Liu (University of Mannheim, Department of Economics, 2018)
We evaluate manufacturing firms' responses to changes in the real exchange rate (RER) using detailed firm-level data for a large set of countries for the period 2001-2010. We uncover the following stylized facts: In export-oriented emerging Asia, real depreciations are associated with faster growth of firm-level TFP, higher sales and cash-flow, and higher probabilities to engage in R&D and to export. We find negative effects for firms in other emerging economies, which are relatively more import dependent, and no significant effects for firms in industrialized economies. Motivated by these facts, we build a dynamic model in which real depreciations raise the cost of importing intermediates, affect demand, borrowing-constraints and the profitability of engaging in innovation (R&D). We decompose the effects of RER changes on productivity growth across regions into these channels. We estimate the model and quantitatively evaluate the different mechanisms by providing counterfactual simulations of temporary RER movements and conduct several robustness analyses. Effects on physical TFP growth, while different across regions, are non-linear and asymmetric.
urn:nbn:de:bsz:180-madoc-450523
Keywords: F; O; 330; real exchange rate; innovation; productivity; exporting; importing; financial constraints; firm-level data